behavioral disturbances (Journal of the College of Basic Education, 2023)
Although there is no unified general definition agreed upon for behavioral disorders, the most common definition is the definition that states that behavioral disorders mean behavior that deviates from behavior that is considered normal in a given society in terms of the rate of occurrence, severity, form or duration. This type of behavior occurs frequently and requires intensive and long-term treatment.